Chemical composition of sediments associated with manganese nodules from the Central Pacific Ocean - Andrew C Aplin; David S Cronan (PANGAEA, 2022)
72 surface sediments associated with manganese nodules from 31 sites in the Central Pacific Ocean were obtained during CCOP/SOPAC cruises in 1980, and from the core collections at the University of Hawaii, Scripps Institution of Oceanography and Lament Doherty Geological Observatory. Prior to chemical analysis, sediment samples were examined in smear slides. Bulk chemical analyses of air-dried samples were made by atomic absorption spectrophotometry for Mn, Fe, Cu, Ni, Co, Pb. Zn, Ca, Al and Ti. Accuracies, determined by comparison with international nodule standards, were better than 10% for all elements except AI (15%), whilst precisions were generally better than 5%. Zn contamination from core barrels was suspected in some samples, and these results were not used.